1998
DOI: 10.1056/nejm199808203390803
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Nonoxynol 9 Film to Reduce Male-to-Female Transmission of Sexually Transmitted Diseases

Abstract: The use of a nonoxynol 9 vaginal film did not reduce the rate of new HIV, gonorrhea, or chlamydia infection in this group of sex workers who used condoms and received treatment for sexually transmitted diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(120 citation statements)
references
References 26 publications
0
118
0
2
Order By: Relevance
“…They are used to orally deliver pain medications, vitamins, and supplements (65)(66)(67). Microbicide drugs, such as dapivirine, retrocyclin-101, cellulose acetate phthalate, and dapivirine in combination with TFV, have been formulated into films for vaginal use, and VCF containing nonoxynol-9, a VCF lubricating film, and a vaginal cleansing film (Apothecus Pharmaceuticals) are all available commercially (25,(28)(29)(30)(31)(32). It is important to evaluate the safety of topical PrEP products, as any breach to the integral mucosal barrier and the associated inflammation promote the recruitment of local CD4 T cells and facilitate HIV infection (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are used to orally deliver pain medications, vitamins, and supplements (65)(66)(67). Microbicide drugs, such as dapivirine, retrocyclin-101, cellulose acetate phthalate, and dapivirine in combination with TFV, have been formulated into films for vaginal use, and VCF containing nonoxynol-9, a VCF lubricating film, and a vaginal cleansing film (Apothecus Pharmaceuticals) are all available commercially (25,(28)(29)(30)(31)(32). It is important to evaluate the safety of topical PrEP products, as any breach to the integral mucosal barrier and the associated inflammation promote the recruitment of local CD4 T cells and facilitate HIV infection (68).…”
Section: Discussionmentioning
confidence: 99%
“…Other promising attributes, such as no leakage, lack of feeling the product inside, likelihood to use the product in the future, and acceptability among their male partners were also described for the films (15). A vaginal contraceptive film (VCF) containing the spermicide nonoxynol-9 was the first commercially available film (25). Other feminine hygiene products, including a VCF lubricating film and a vaginal cleansing film, are also marketed.…”
mentioning
confidence: 99%
“…The results of these studies justified proceeding to efficacy trials, and two such trials were reported by the end of 1999. 7 8 Their results, and preliminary results from a study in commercial sex workers, suggest that nonoxinol 9 actually increases HIV transmission, probably because of local genital toxicity. The toxicity in these studies may have been associated with frequency of use, and analyses to address this are under way.…”
Section: Status Of Microbicides Tested In Human Trialsmentioning
confidence: 94%
“…Although lack of benefit may seem implausible on the basis of preclinical and early clinical studies, the experience with nonoxinol 9 shows that promising products may prove ineffective or even harmful in efficacy trials. 7 8…”
Section: Challenges For Evaluationmentioning
confidence: 99%
“…However, around the time these data were published in the 1990s, doubts emerged about the protective effect [12][13][14][15] ; then, studies showed that detergents might actually increase the risk of transmission [16][17][18][19] . It appeared that N-9 can break up the cell lining or irritate the epithelium of the vagina (and the rectum) and that it kills the normal vaginal flora, thus making it easier for a virus or other infective organism(s) to invade.…”
Section: S P E R M I C I D E S a N D S E X U A L L Y T R A N S M I T mentioning
confidence: 99%